Treatment of Anxiety and Depression in a Patient with Brugada Syndrome - Jasper J. Chen (Case Reports in Psychiatry, 2014)
Background. Brugada syndrome is rare and has been a clinically diagnosable entity since 1992. Its clinical manifestations are highly variable, and while some patients remain asymptomatic, others endure sudden cardiac death. Initial presenting symptoms may include palpitations, seizures, syncope, and nocturnal agonal respiration. The diagnosis of Brugada syndrome relies on both clinical findings and characteristic ECG patterns that occur spontaneously or are induced by usage of sodium-channel blocking agents. Aims of Case Report. Many psychiatrists may be unaware of the possibility of medical cocontributing etiologies to physical symptoms of anxiety and depression. We present a case of a patient who was treated psychiatrically for anxiety and panic attacks and who was subsequently diagnosed with Brugada syndrome and treated medically with an implantable cardioverter defibrillator (ICD), the only treatment option demonstrated to be effective. Her psychiatric symptoms predated her diagnosis of Brugada syndrome by at least fifteen years. Conclusion. The patient's eventual diagnosis of Brugada syndrome altered the course of her psychopharmacologic medication management and illustrates the utility of a psychosomatic approach to psychiatric symptom management.